Morphology and molecular identification of the trematode Echinostoma revolutum metacercariae, as a new parasite of amphibians in Uzbekistan - ELMUROD E. IKROMOV; ERKIN F. IKROMOV; HIKMET SAMI YILDIRIMHAN; NURHAN SÜMER; LAYLO AKMURADOVA; ABDURAHMON YUSUPOV; OYBEK O. AMIROV; ILHOMJON RUSTAMOV; BEKZOD USMONOV (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ikromov EE, Ikromov EF, Yildirimhan HS, Sümer N, Akmuradova L, Yusupov A, Amirov OO, Rustamov I, Usmonov B. 2025. Morphology and molecular identification of the trematode Echinostoma revolutum metacercariae, as a new parasite of amphibians in Uzbekistan. Biodiversitas 26: 4412-4423. This study examined the helminth fauna of two frog species, Pelophylax terentievi, Pelophylax sp., in eastern (Ferghana Valley: Andijan, Namangan and Ferghana) and central Uzbekistan (Bukhara, Navoi and Samarkand regions). We identified the metacercarium trematode Echinostoma revolutum, for the first time in this context, which is an intestinal parasite commonly found in various waterfowl. At the same time, we studied amphibians for the first time as new intermediate hosts of the parasite. This article discusses the morphology and molecular characteristics of E. revolutum found in the eye cavities, kidneys and body cavities of P. terentievi and Pelophylax sp. in the central and eastern geographical regions of Uzbekistan. Our analyses showed that the trematode, E. revolutum, differs morphologically from other ecomorphs in terms of body size, cyst diameter and localization. This study also provided molecular data for the genus Echinostoma in the ITS1+5.8S+ITS2 regions of ribosomal DNA, forming a well-supported clade in the phylogenetic tree. The sample we examined, E. revolutum (UZ), was in the monophyletic group together with a sample extracted from the NCBI database (E. revolutum MZ409811) and had a common ancestor. These results provide molecular evidence to support the identification of E. revolutum species in our study. In addition, our analysis showed that Echinostoma sp. MZ409812 is a sister group to E. revolutum (clade J). E. miyagavai (clade I), E. nasincovae (clade L), E. paraensei and E. maldonadoi (clade M) are the closest groups to E. revolutum. Our results contribute to the understanding of the species and genetic diversity of the genus Echinostoma and the species E. revolutum. The high infection rate (up to 14%) of the amphibians P. terentievi and Pelophylax sp. with these parasites indicates a significant biological threat, which requires enhanced monitoring and development of measures to protect waterfowl in the region, underscoring the importance of this study in preserving the ecological balance.